Internalizing the Value of Respecting Differences through Role Playing: Classroom Action Research on Islamic Education Learning in Elementary Schools - Mushoffa, Moh. Hadziq; Husnul Khotimah; Himma, Husnul (FITK UIN Walisongo Semarang, 2025)
Life in a pluralistic society requires the formation of noble morals from an early age, especially an attitude of mutual respect for differences. However, moral learning in Islamic Religious Education (PAI) subjects in elementary schools often experiences obstacles because student learning outcomes, especially in the realm of social attitudes, are still low and have not reached the Minimum Completeness Criteria (KKM). This study aims to analyze the application of the Role Playing Learning Model in improving the moral learning outcomes of students in grade Va of SDN 1 Kalipucangkulon Welahan Jepara on the material of mutual respect for differences in the 2024/2025 school year. The research uses a classroom action research (PTK) approach with a spiral design consisting of three stages: pre-cycle, cycle I, and cycle II. The subjects of the study were 25 students of class Va. Data were collected through behavioral observation, attitude assessment documentation, and field notes, then analyzed descriptively, qualitatively, and quantitatively. The results showed an increase in moral learning completeness from 58% in the pre-cycle to 76% in the first cycle, and reached 88% in the second cycle. The application of Role Playing has been shown to be effective in helping students understand moral values contextually through simulation of real social experiences, thus facilitating the internalization and application of an attitude of respect for differences in daily life. These findings make an original contribution to the development of social-emotional experience-based PAI learning strategies, while offering innovative alternatives for teachers in optimizing moral learning in elementary schools